Priorities and Incentives for the Mobility of Russian IT Specialists - P. P. Deryugin; S. V. Rasskazov; S. D. Kurazhev; Zhao Jie; E. A. Esselevich (Дискурс, 2024)
Introduction. The mobility of IT specialists differs from the mobility of all other socioprofessional groups. The study of mobility is relevant, since the movement of IT specialists significantly affects the peculiarities of the formation of the digital space, the success of many types of activities of modern society, and its prospects. Sociology has accumulated a scientific foundation for covering mobility based on new research principles, which makes it possible to identify specific characteristics of the mobility of IT specialists.Methodology and sources. The conceptual theoretical and methodological positions of the study are represented by a complex of ideas, the basis of which is the work of P.A. Sorokin and his followers a bout the essence of mobility. The article is based on ideas a bout the mobile society formulated in the works of D. Urry, M. Castells, B. Latour, K. Knorr-Cetina, and the provisions of the works of D.V. Ivanov about new forms of integration of the digital and streaming society, where the mobility of IT specialists begins to play a new, more important role. A number of sources were used, where attention was paid to the analysis of the mobility of Russian IT specialists as a phenomenon reflecting the characteristics of their movements in the conditions of modern Russian society.Results and discussion. Two main results of the study show, firstly, that the professional component of the mobility of IT specialists is an active beginning of movements and changes – their mobility. Ultimately, the professional mobility of IT specialists is aimed at finding the most suitable social environment that allows them to successfully implement their professional activities. Secondly, it was revealed that the specifics of the work activities of IT specialists form the motivation for changes and movements, where personal interests can be very significant and do not always coincide with the interests of IT organizations.Conclusion. Analysis of the generalized materials allows us to characterize some prospects and incentives for the mobility of Russian IT specialists, to formulate the author’s definition of mobility as a phenomenon determined by the social and professional attributes of the digital space, as well as the goals of mobility, as achieving the most adequate conditions for professional self-realization, as well as ensuring preservation and correction professional identity in the IT space.